Case Report: Successful treatment of pulmonary lymphomatoid granulomatosis with a PD-1 inhibitor-based regimen - Liu, Xiaoyan; Gao, Qi; Wu, Feifei; Jia, Junli; Cao, Li; Yu, Qingfeng; Zhang, Dandan; Zhao, Wugan; Ma, Jie (Frontiers in Oncology, 2026)
Pulmonary lymphomatoid granulomatosis (PLG) is a rare and aggressively progressive tumor characterized by atypical clinical manifestations and pathological features. This condition is highly prone to misdiagnosis and underdiagnosis. The absence of standardized treatment regimens has resulted in diverse recommendations in the literature, predominantly favoring rituximab-based therapies. However, the prognosis for these patients remains poor, with a median survival time of only 14 months. Recently, we encountered a case of PLG exhibiting programmed cell death-1 (PD-1), PD-L1, and p53 expression. The patient was treated with a PD-1 inhibitor-based regimen. Remarkably, the patient achieved an overall survival (OS) of 52 months at the most recent follow-up, without disease progression. This case stands as a notable observation, particularly because the utilization of a PD-1 inhibitor-based regimen has not been previously reported for PLG treatment. We hope this case will contribute significantly to enhancing physicians’ understanding of PLG and provide a new potential treatment strategy.